2012
DOI: 10.1021/cg2010858
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Rational Design of Crystalline Surfaces for Heteroepitaxy: Role of Molecular Functionality

Abstract: The rational design of crystalline surfaces for controlling nucleation and crystal growth via heteroepitaxial mechanisms is of great importance in the manufacture of advanced functional materials, such as pharmaceuticals and semiconductors. Despite numerous studies investigating the singular effect of crystalline lattice matching, molecular functionality, or topography on epitaxial ordering, no study has been carried out investigating these effects in competition with one another in order to establish which ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(109 citation statements)
references
References 29 publications
1
108
0
Order By: Relevance
“…42,44 These parameters and the size of the overlayer are required to perform the calculations. The default setting for overlayer size (25b 1 *25b 2 ) was used in every case.…”
Section: Resultsmentioning
confidence: 99%
“…42,44 These parameters and the size of the overlayer are required to perform the calculations. The default setting for overlayer size (25b 1 *25b 2 ) was used in every case.…”
Section: Resultsmentioning
confidence: 99%
“…Isomorphous compounds like flufenamic acid (Lee et al, ) and dihydro‐carbamazepine (Srirambhatla et al, ) facilitated crystallization of mefenamic acid and carbamazepine, respectively, by LDE. Crystallization of paracetamol (PCM) on biocompatible carbohydrates had LDE as the most common underlying mechanism (Chadwick, Chen, Myerson, & Trout, ; Quon et al, ; Wijethunga, Baftizadeh, Stojaković, Myerson, & Trout, ). Vilmali et al reported a significant decrease in nucleation induction time for crystallization of metastable polymorph of mefenamic acid with polymeric nanoconfinement with a dihedral angle of 90° (López‐Mejías et al, ).…”
Section: Mechanisms Governing Heteronucleationmentioning
confidence: 99%
“…Air‐jet in the supersaturated solution of the API has also been investigated as one of the approaches, wherein the air bubble served as a heterosurface (Capellades et al, ). Intentional incorporation of the heterosurface in the process has been widely studied to understand the role of the surface topography and surface chemistry on the crystallization of the API (Arribas Bueno et al, ; Arribas Bueno, Crowley, Hodnett, Hudson, & Davern, ; Chadwick et al, ; Padrela et al, ; Quon et al, ). Current section deals with the variety of heterosurfaces that have been employed for pharmaceutical heterogeneous crystallization.…”
Section: Types Of Heteronucleantsmentioning
confidence: 99%
See 2 more Smart Citations